Gastrointestinal symptoms in atopic eczema. Issue 3 (1st March 1998) - Caffarelli, Carlo; Cavagni, Giovanni; Deriu, Franca M; Zanotti, Paola; Atherton, David J
Abstract : AIMS: To determine the prevalence of gastrointestinal symptoms in children with eczema and the association of such symptoms with the extent of eczema or skin prick test results. METHODS: Sixty five children with atopic eczema and a control group matched for age and sex were recruited. Their parents completed a questionnaire about the children's gastrointestinal symptoms. The children's skin was examined; their weight, height, and abdominal circumference were measured; and skin prick tests were carried out. RESULTS: Gastrointestinal symptoms, especially diarrhoea, vomiting, and regurgitation, were more common in the children with eczema. Diarrhoea appeared to be associated with the ingestion of specific foods. Gastrointestinal symptoms were related to diffuse eczema and positive skin prick tests to foods. There was no anthropometric differences between the patient and control groups. CONCLUSIONS: A gastrointestinal disorder is common in children with eczema, especially with diffuse distribution. This may be responsible for substantial symptoms and may play a part in the pathogenesis of the disease and in the failure to thrive with which it is sometimes associated.